Analisis Strategi pemasaran dalam meningkatkan volume penjualan pada PT. Aneka Gas Industri Tbk - Ayu Lestari Sinambela; Fenny Krisna Marpaung (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
Marketing strategy in increasing sales volume at PT. Aneka Gas Industri Tbk, Medan aims to find out and learn how the general condition profile in marketing at the company, through identification and analysis of internal and external factors that exist in PT. Aneka Gas Industri Tbk, Medan. To find out how the strategy of PT. Aneka Gas Industri Tbk, Medan in increasing sales in market share and competing with other industrial gas companies and knowing the strategies used by PT, Aneka Gas Industri Tbk, Medan in increasing sales volume. The method used to find out how the company is able to increase sales volume is by analyzing the marketing mix strategy or often known as the 4P of marketing, namely: "product (product), price (price), place (place) and promotion (promotion). )". For data collection, qualitative descriptive or using primary and secondary data sources through in-depth interviews, data collection and exploration